2015
DOI: 10.1007/s00726-015-2036-8
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal taurine and alanine modulate anxiety-like behavior and decelerate cortical spreading depression in rats previously suckled under different litter sizes

Abstract: The amino acids taurine and alanine play a role in several physiological processes, including behavior and the electrical activity of the brain. In this study, we investigated the effect of treatment with taurine or alanine on anxiety-like behavior and the excitability-dependent phenomenon known as cortical spreading depression (CSD), using rats suckled in litters with 9 and 15 pups (groups L9 and L15). From postnatal days 7 to 27, the animals received per gavage 300 mg/kg/day of taurine or alanine or both. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 54 publications
5
15
0
Order By: Relevance
“…Taurine pre-administered to CUMS rats could significantly inhibit the decrease of sucrose consumption, exploration ability, horizontal score and vertical score in the OFT, and number of platform crossings in the MWM, while hinder the increase of the moving distance and latency in the MWM, indicating an obvious preventive effect of taurine on the depression-like behavior. The results were similar to those from an experiment on young rats, in which taurine exerted important anti-anxiety effects 18 , and also in accordance with the results that taurine pretreatment prevented anesthetic isoflurane-induced cognitive impairment in rats 19 . We also found that taurine supplemented to control rats had no significant effects on behavior, which was in accordance with previous studies that added taurine to normal animals 20 .…”
Section: Discussionsupporting
confidence: 90%
“…Taurine pre-administered to CUMS rats could significantly inhibit the decrease of sucrose consumption, exploration ability, horizontal score and vertical score in the OFT, and number of platform crossings in the MWM, while hinder the increase of the moving distance and latency in the MWM, indicating an obvious preventive effect of taurine on the depression-like behavior. The results were similar to those from an experiment on young rats, in which taurine exerted important anti-anxiety effects 18 , and also in accordance with the results that taurine pretreatment prevented anesthetic isoflurane-induced cognitive impairment in rats 19 . We also found that taurine supplemented to control rats had no significant effects on behavior, which was in accordance with previous studies that added taurine to normal animals 20 .…”
Section: Discussionsupporting
confidence: 90%
“…These molecules play key roles in excitatory and inhibitory transmission in the brain. 55 The opposite changes in ethanolamine and asparagine levels in the PFC and hippocampus suggest that these brain regions may show different responses to DG. Further studies are needed to clarify the differential effects of DG in the brain and to further elucidate the specific metabolite changes and pathways involved.…”
Section: Discussionmentioning
confidence: 99%
“…However, taurine does play other critical roles, particularly in the central nervous system, such as by helping to regulate cell volume and modulate neurotransmission in the brain (Oja & Saransaari, 2017). In addition, taurine has been hypothesized to play a role in anxiolytic behavior in rodents (Chen et al, 2004; El Idrissi et al, 2009; da Silva Francisco & Guedes, 2015; Kong et al, 2006; McCool & Chappell, 2007; Wu et al, 2017; Zhang & Kim, 2007). The effects of caffeine and taurine in combination have mainly been studied in the context of physical performance and cardiovascular function.…”
Section: Introductionmentioning
confidence: 99%